Digital Literacy and Critical Thinking in Relation to EFL Writing Performance - Pinkan Auliyani; Nur Hidayat (ITScience (Information Technology and Science), 2026)
Writing has always been one of the most challenging skills for students in an English as a Foreign Language context. This skill not only requires language proficiency but also involves strong critical thinking skills to organize ideas.This study examined the relationship between digital literacy, critical thinking skills, and English writing performance among EFL students. This study applied a quantitative approach with a correlational design.The study participants were 37 students in the English Language Education program at Muhammadiyah University of Surakarta, chosen using purposive sampling. Researchers collected data from students’ writing scores given by lecturers using the ESL Composition Profile rubric, and from questionnaires regarding digital literacy and critical thinking skills. Because the collected data were not normally distributed, Spearman's rank correlation coefficient was used in the analysis.The results showed that digital literacy was not significantly corelated with students' writing performance (rho = -0.060, p = 0.725). Similarly, critical thinking skills were not significantly correlated with writing performance (rho = 0.170, p = 0.313), although the coefficient value for critical thinking was numerically higher. Interestingly, digital literacy and critical thinking skills were found to have moderate and significantly correlation with each other (rho = 0.471, p = 0.003). This study concludes that digital literacy and critical thinking as measured in this study, were not significantly correlated with EFL students writing performance, suggesting that other factors, such as grammar mastery, may play a larger role. These findings also indicate that digital literacy and critical thinking skills are interrelated as cognitive abilities.